2023
DOI: 10.2217/pmt-2022-0065
|View full text |Cite
|
Sign up to set email alerts
|

Epidural Dexamethasone for Acute Postoperative Pain Management: A Systematic Review with Meta-Analysis

Abstract: Aim: To study the effect of epidural dexamethasone in postoperative pain management. Methods: Random-effects meta-analysis was conducted in RevMan 5.4. Results: We included nine randomized-controlled trials (RCT) with 657 patients. Dexamethasone demonstrated longer analgesia duration (mean difference 266.18 minutes, 95% CI [3.21,529.14]; p 0.05), lower incidence of nausea and vomiting during the first postoperative day (risk ratio 0.36, 95% CI [0.18,0.71]; p 0.004), and lower antiemetic requirements (risk rati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 52 publications
0
0
0
Order By: Relevance
“…In this study, a dosage of 8 mg of dexamethasone was selected. Although the exact mechanism and site of action of dexamethasone in reducing PONV are not fully understood, it is suggested that it may inhibit prostaglandins or release endorphins, which can improve mood, enhance wellbeing, and increase appetite (Abdildin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, a dosage of 8 mg of dexamethasone was selected. Although the exact mechanism and site of action of dexamethasone in reducing PONV are not fully understood, it is suggested that it may inhibit prostaglandins or release endorphins, which can improve mood, enhance wellbeing, and increase appetite (Abdildin et al, 2023).…”
Section: Discussionmentioning
confidence: 99%